New, Oliver (London, 2013)
2013 "New, Oliver", 2013, HistoryTalk Oliver came to London from Cardiff and recalls the range of industries in west London. He worked at an offshoot of EMI in Hayes initially doing warehousing and distribution work. He changed jobs frequently in this period, working on various industrial estates. He then joined London transport in 1981 to be a guard and trained at the White City training Centre. He comments on the west London engineering corridor with its skilled AEU workforce and railway section mainly on the underground lines/ depots. He worked at Northfields depot on the Piccadilly Line and then Acton Town. Describes working at depots as part of a train- crew and the various traditions and mess- rooms as well as the African Caribbean managers and racism. Notes the seniority system and the sense of fairness and solidarity on the job. Describes the then system of cleaning and the status of cleaners and the later privatisation of cleaning services. Outlines the shift systems and the introduction of OPO trains and the resulting loss of guards jobs in the 1980s. describes some aspects of working as a motorman and the system for dealing with drivers after track suicides. He was on full- time release for union work from 1981 and seconded to the RMT in 2007. Discusses the future of London Transport.